2015
DOI: 10.1186/s12958-015-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester diagnosis and management of Cesarean scar pregnancies after in vitro fertilization-embryo transfer: a retrospective clinical analysis of 12 cases

Abstract: BackgroundAlthough Caesarean scar pregnancy (CSP) is rare, it can cause life-threatening complications. The increasing rate of Cesarean delivery plus rapid development of in vitro fertilization-embryo transfer (IVF-ET) may increase the occurrence of CSP as well as the ratio of heterotopic CSP (HCSP)/CSP. Therefore, early diagnosis and management of CSP are necessary to avoid serious complications. And the purpose of this article is to evaluate the importance and feasibility of the first-trimester diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…High-resolution vaginal ultrasonography is the preferred diagnostic method for HCSP, and the mean gestational age at CSP diagnosis is reported to be 7.5±2.5 weeks [11]. Ouyang et al [4] showed that the gestational age ranged from 5 weeks and 3 days to 7 weeks and 4 days in CSP and from 5 weeks and 6 days to 7 weeks and 4 days in HCSP using transvaginal color Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…High-resolution vaginal ultrasonography is the preferred diagnostic method for HCSP, and the mean gestational age at CSP diagnosis is reported to be 7.5±2.5 weeks [11]. Ouyang et al [4] showed that the gestational age ranged from 5 weeks and 3 days to 7 weeks and 4 days in CSP and from 5 weeks and 6 days to 7 weeks and 4 days in HCSP using transvaginal color Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study, we conducted a search and review of the literature pertaining to HCSP. To the best of our knowledge, a total of 23 cases of HCSP have been reported in the English literature [2, 4, 10, 1226], and the results are summarized in Additional file 1: Table S1. The reported treatments included conservative management, fetal reduction by potassium chloride, laparoscopic excision, aspiration of embryonic or ectopic gestational sac, hysteroscopy with directed evacuation, injection of a mixture of MTX and KCl, or laparotomic excision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations